RETRACTION Wayoi, D. S., Setyawan, H., Suyanto, S., Prasetyo, Y., Lastiono, S. T.., Nurkadri, N., Putro, B. N., Harmanto, H., Darmawan, A., HB, G., & Eken, Özgür. (2024). Implementación de la gestión del programa de educación física para los pacientes de rehabilitación de drogas en el centro de terapia para drogadictos (Implementing management of the physical fitness education program for the drug rehabilitation patients in drug addict therapy centre). Retos, 60, 309–319. https://doi.org/10.47197/retos.v60.104433 - RETOS, RETOS (Retos, 2025)
Wayoi, D. S., Setyawan, H., Suyanto, S., Prasetyo, Y., Lastiono, S. T.., Nurkadri, N., Putro, B. N., Harmanto, H., Darmawan, A., HB, G., & Eken, Özgür. (2024).  Implementación de la gestión del programa de educación física para los pacientes de rehabilitación de drogas en el centro de terapia para drogadictos (Implementing management of the physical fitness education program for the drug rehabilitation patients in drug addict therapy centre). Retos, 60, 309–319. https://doi.org/10.47197/retos.v60.104433Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 12Authors in the published PDF with modified authors: 11Differences between the authors between both moments: +7 y -8 (Additions: Suyanto, Yudik Prasetyo, Nurkadri, Baskoro Nugroho Putro, Harmanto, Arief Darmawan, Özgür Eken. Eliminated: José Vicente García-Jiménez, Ratko Pavlovic, Agnieszka Magdalena Nowak, Nugroho Susanto, Ari Wibowo Kurniawan, Abdul Aziz Purnomo Shidiq, Roziah, Khoiril Anam)